Analysis of timesharing in Latin America - Rojas Ulloa, Milushka Felicitas (2022)
The purpose of this article is to know the regulation of timeshare in the main legal systems of Latin America that lead the tourism-vacation business, with the objective to compare the legal nature of this institution in each legislation; that is, analyze whether it was recognized as a real right or a personal right. Therefore, we will seek to find out if the regulation in our national legislation is appropriate, or if some modifications should be projected that would allow our country to compete on equal terms with other countries in the world.